Mapping QTLs Controlling Flowering Time and Important Agronomic Traits in Pearl Millet - Kumar, Sushil; Hash, C. Tom; Nepolean, T.; Satyavathi, C. Tara; Singh, Govind; Mahendrakar, Mahesh D.; Yadav, Rattan S.; Srivastava, Rakesh K. (Frontiers in Plant Science, 2017)
Pearl millet [Pennisetum glaucum (L.) R. Br.] is a principal staple food for the people of arid and semi-arid regions of the world. It is fast gaining importance as a climate resilient nutricereal. Exploiting the bold seeded semi-dwarf early flowering genotypes in pearl millet is a key breeding strategy to enhance yield, adaptability, and for adequate food in resource-poor zones. Genetic variation for agronomic traits of pearl millet inbreds can be used to dissect complex traits through quantitative trait locus (QTL) mapping. This study was undertaken to map a set of agronmoically important traits like flowering time (FT), plant height (PH), panicle length (PL), and grain weight (self and open pollinated seeds) in the recombinant inbred line (RIL) population of ICMB 841-P3 × 863B-P2 cross. Excluding grain weight (open pollinated), heritabilities for FT, PH, PL, grain weight (selfed) were in high to medium range. A total of six QTLs for FT were detected on five chromosomes, 13 QTLs for PH on six chromosomes, 11 QTLs for PL on five chromosomes, and 14 QTLs for TGW spanning five chromosomes. One major QTL on LG3 was common for FT and PH. Three major QTLs for PL, one each on LG1, LG2 and LG6B were detected. The large effect QTL for TGW (self) on LG6B had a phenotypic variance (R2) of 62.1%. The R2 for FT, TGW (self), and PL ranged from 22.3 to 59.4%. A total of 21 digenic interactions were discovered for FT (R2=18-40%) and PL (R2=13-19%).The epistatic effects did not reveal any significant QTL × QTL × environment (QQE) interactions. The mapped QTLs for flowering time and other agronomic traits in present experiment can be used for marker-assisted selection (MAS) and genomic selection (GS) breeding programs.